1997
DOI: 10.1007/s002239900214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lead on Bone Development and Bone Mass: A Morphometric, Densitometric, and Histomorphometric Study in Growing Rats

Abstract: The effect of exposure to lead on the longitudinal development of bone and on bone mass was studied in rats. A group of 35, 50-day-old female Wistar rats was divided into a control group of 15 rats and an experimental group of 20 rats fed a diet supplemented with 17 mg of lead acetate per kg feed for 50 days. Total body bone densitometry (TBBMC) was performed the day before ending the 50-day experiment. On day 50, all rats were killed and their right femur and 5th lumbar vertebra were dissected. The bones were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…Because of the influence of weight on bone mass [11], femur BMC was corrected for the animals final body weight (femur BMC/FW mg/g). As in our earlier studies [11][12][13][14], we have relied on DXA (Norland XR-26, Norland Co., Fort Atkinson, Wisconsin, USA). Our coefficients of variation (CV) for the current measurements, determined by six separate measurements done on three rat femurs and 5th vertebras at intervals of 3-4 days were 0.8% and 0.7%, respectively.…”
Section: Morphometric and Densitometric Studiesmentioning
confidence: 99%
“…Because of the influence of weight on bone mass [11], femur BMC was corrected for the animals final body weight (femur BMC/FW mg/g). As in our earlier studies [11][12][13][14], we have relied on DXA (Norland XR-26, Norland Co., Fort Atkinson, Wisconsin, USA). Our coefficients of variation (CV) for the current measurements, determined by six separate measurements done on three rat femurs and 5th vertebras at intervals of 3-4 days were 0.8% and 0.7%, respectively.…”
Section: Morphometric and Densitometric Studiesmentioning
confidence: 99%
“…After bone densitometry, the femurs were processed using techniques described elsewhere [16][17][18] for the histomorphometric study of nondecalcified bone. The bones were sectioned longitudinally into 7-micra slices using a Microm microtome (Microm, Heidelberg, Germany) and were stained with Goldner stain.…”
Section: Histomorphometric Studiesmentioning
confidence: 99%
“…5 Diseases or states with increased bone turnover, such as osteoporosis, pregnancy, hyperthyroidism and hyperparathyroidism, are associated with increased mobilization of Pb from the skeleton. 6 -8 It has been reported that Pb plays a role in osteopenia 9,10 and inhibits fracture healing. 11 Moreover, intra-articular lead has…”
Section: Introductionmentioning
confidence: 99%